Insect Bioassay in Biosafety Containment to Select Transgenic Rice (Oryza sativa L.) Harboring Cry1B Gene Resistant to Yellow Stem Borer (Scrirpophaga incertulas Walk.) - Estiati, Amy; Nurhasanah, Ade Nena; Nugroho, Satya (Annales Bogorienses, 2013)
Development of rice varieties resistant to yellow stem borer (YSB) is very crucial. Agrobacterium-mediated transformation of cry1B gene under wound inducible gene promoter mpi (maize proteinase inhibitor) into a local rice variety Rojolele had been conducted. PCR analysis proved that cry1B gene had been integrated into plant genome of 3R25 and 3R5 rice lines. Segregation analysis using PCR for cry1B gene of the two putative transgenic rice lines at third (T2), fourth (T3), fifth (T4), and sixth (T5) generations of 3R25 and 3R5 lines proved that 3R25.7.27, 3R25.7.13.8.2, 3R25.7.13.8.6, 3R25.7.13.8.8, 3R5.26.2, and 3R5.26.5 are homozygous lines for cry1B gene. Insect bioassay on three randomly picked homozygous transgenic rice lines to study the efficacy of cry1B gene toward YSB was conducted in biosafety containment by infestingYSB larvae at first instar into 3R25.7.27, 3R25.7.13.8.6, and 3R5.26.5 transgenic rice lines, using non--transgenic Rojolele, IR64 and IR74 as susceptible controls. The results showed that the percentages of deadhearts symptoms of 3R25.7.27, 3R5.26.2, and 3R25.7.13.8.6 rice lines were lower than those of the susceptible control lines with scores of 0.1 and 0, respectively. While the scores of all three susceptible control plants were 9. The results proved that lines 3R25.7.27, 3R25.7.13.8.6, and 3R5.26.2 were categorized as resistant lines while the non-transgenic Rojolele, IR64, and IR74 were categorized as susceptible lines. The results also showed that the cry1B gene was expressed and produced insecticidal protein CRY1B which were active against YSB to protect rice plant toward YSB infestation.